Inkulturasi Gereja Katolik dengan Kebudayaan Dayak Pompakang dalam Prosesi Ngongkat Salib: Perspektif Sosiologi Agama Robert J. Schreiter - Valentino Dwika Damara; Tedjo Setiyoko; Yly Suardy; Yulius Roge Paliling; Herkulana M. Soeryamassoka (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2025)
The inculturation of the Catholic Church's faith in the context of local culture is a strategic issue in contemporary missiology, especially in the territory of indigenous peoples of Indonesia. This study examines the process of inculturation of the Catholic Church with the Dayak Pompakang culture, focusing on the traditional prosesion of “Ngongkat Salib’' (raising the cross in local religious ceremonies), through the framework of Robert J. Schreiter's sociological theory of religion. The research method uses a qualitative ethnographic approach, collecting data through in-depth interviews with religious and community leaders, participatory observation of rituals, and an examination of Church documents and traditional Dayak Pompakang literature. The study's results demonstrate that the “Ngongkat Salib” embodies the transformation of Christian symbols into a form that integrates local cultural identities, resulting in an authentic communication of faith that is both respectful and sincere. This process of inculturation is not just syncretism, but a genuine dialogue in which Christian values and Dayak local wisdom enrich each other. Schreiter's theory of “Constructing Local Theologies” proves relevant in explaining how the Catholic Church facilitates meaningful encounters between universal faith and specific cultural contexts. The academic implications of this research enrich the discourse of the sociology of religion and missiology in Southeast Asia, while pastorally offering an inculturation model that can be applied in contextual evangelization in other indigenous territories. Research confirms that deep inculturation requires a dialogical approach, respect for cultural heritage, and theological openness to dynamic changes in the lives of local people.